Author Correction: Discovery and refinement of genetic loci associated with cardiometabolic risk using dense imputation maps. (December 2018) - Iotchkova, Valentina; Huang, Jie; Morris, John; Jain, Deepti; Barbieri, Caterina; Walter, Klaudia; Min, Josine; Chen, Lu; Astle, William; Cocca, Massimilian; Deelen, Patrick; Elding, Heather; et al.
In the version of the article published, the surname of author Aaron Isaacs is misspelled as Issacs.